Evaluation of Visibility of Foreign Bodies in the Maxillofacial Region: Comparison of Computed Tomography, Cone Beam Computed Tomography, Ultrasound and Magnetic Resonance Imaging - Valizadeh, Solmaz (Iran J Radiol, 2016)
BACKGROUND: Detection of foreign bodies (FBs) is challenging. Selection of a fast and affordable imaging modality to locate the FB with minimal patient radiation dose is imperative. OBJECTIVES: This study sought to compare four commonly used imaging modalities namely cone beam computed tomography (CBCT), magnetic resonance imaging (MRI), computed tomography (CT), and ultrasound (US) for detection of FBs in the head and neck region. MATERIALS AND METHODS: In this in vitro study, iron, glass, stone, wood, asphalt, and tooth samples measuring 0.1 × 0.5 × 0.5 cm were placed in the tongue muscle, soft tissue-bone interface and nasal cavity in a fresh sheep’s head and subjected to MRI, US, CT and CBCT. A total of 20 images were captured by each imaging system from the six materials in the afore-mentioned locations. The images were observed by an expert oral and maxillofacial radiologist and a general radiologist. To assess reliability, 20 images were randomly observed by the observers in two separate sessions. The images were classified into three groups of good visibility, bad visibility and invisible. The data were analyzed using SPSS version 18, Wilcoxon Signed Rank, Pearson chi square, and Fisher’s exact tests. RESULTS: All FBs in the tongue and at the soft tissue-bone interface had good visibility on US (P = 1.00). Also, CBCT and CT had significantly different performance regarding FB detection (P < 0.001). All wooden samples in the nasal cavity were invisible on CT scans; while, only 20% of them were invisible on CBCT scans. MRI showed significant differences for detection of FBs in the three locations (P < 0.001). MRI could not locate iron samples due to severe artifacts and only showed their presence (bad visibility) but other FBs except for wood and tooth in the nasal cavity (100% invisible) had good visibility on MRI. CONCLUSIONS: Ultrasound is recommended as the first choice when FB is located within the superficial soft tissues with no bone around it. In case of penetration of FB into deeper tissues or beneath bone, CT or CBCT are recommended. Otherwise, considering lower dose, CBCT is preferred over CT. We can use MRI if the FB is not ferromagnetic. However, CT is the first choice in emergency situations because of higher sensitivity.